2011
DOI: 10.1186/1746-6148-7-30
|View full text |Cite
|
Sign up to set email alerts
|

The increase of methicillin-resistant Staphylococcus aureus(MRSA) and the presence of an unusual sequence type ST49 in slaughter pigs in Switzerland

Abstract: BackgroundIn years past, methicillin-resistant S. aureus (MRSA) has been frequently detected in pigs in Europe, North America and Asia. Recent, yet sporadic studies have revealed a low occurrence of MRSA in Switzerland. In 2009, a monitoring survey of the prevalence and genetic diversity of methicillin-resistant S. aureus (MRSA) in slaughter pigs in Switzerland was conducted using methods recommended by the EU guidelines, and using a sampling strategy evenly distributed throughout the year and representative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…This was in agreement with other studies conducted in Switzerland (19,27,34). We speculate that this might be due to differences in the use of antimicrobial agents in farming.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was in agreement with other studies conducted in Switzerland (19,27,34). We speculate that this might be due to differences in the use of antimicrobial agents in farming.…”
Section: Discussionsupporting
confidence: 93%
“…There are few reports of other pig-associated MRSA genotypes that seem rare in humans: CC9, CC1, and CC49 (2,15,27,34,40). Pig-associated ST9 S. aureus can be transmitted to humans who were in contact with pigs (26).…”
mentioning
confidence: 99%
“…While one-third of these tiamulin-resistant MRSA isolates harbored the vga(A)v gene, the remaining isolates did not contain any of the known vga genes (25). In the present study, we characterized a new streptogramin A, pleuromutilin, and lincosamide resistance gene, vga (E).…”
Section: and Vga(d) While Vga(d) Was Identified On A Plasmid In Enmentioning
confidence: 81%
“…During the monitoring of methicillin-resistant Staphylococcus aureus (MRSA) in the nasal cavities of pigs at slaughterhouses in Switzerland in 2009 and 2010, 90% of the MRSA isolates were resistant to tiamulin (25). While one-third of these tiamulin-resistant MRSA isolates harbored the vga(A)v gene, the remaining isolates did not contain any of the known vga genes (25).…”
Section: and Vga(d) While Vga(d) Was Identified On A Plasmid In Enmentioning
confidence: 99%
“…A study by Schmitz et al, in 2001 reported that tetM gene was detected in 76.0% of tetracycline-resistant MRSA, which followed closely by 73.0% of tetK gene (28). Another study also showed that all the MRSA samples collected from nasal cavities in pigs were mostly tetM-positive (29). In addition, tetM gene was also detected in 92.0% of all the tetracycline-resistant MRSA strains isolated in a Spanish hospital (30).…”
Section: Discussionmentioning
confidence: 96%